Benefits trickling away: The health impact of extending access to piped water and sanitation in urban Yemen - Stephan Klasen; Tobias Lechtenfeld; Kristina Meier; Johannes Rieckmann (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
This article investigates the impact of piped water supply and sanitation on health outcomes in urban Yemen using a combination of quasi-experimental methods and results from microbiological water tests. Variations in project roll-out allow separate identification of water and sanitation impacts. Results indicate that access to piped water supply worsens health outcomes when water rationing is frequent, which appears to be linked to a build-up of pollution in the network. When water supply is continuous no clear health benefits are found compared to traditional urban water supply through water vendors. Connections to piped sewers can lead to health improvements, conditional on regular water supply. The findings suggest that investments in piped water supply should not be made when availability and reliability of water cannot be guaranteed.
Keywords: I10; I38; Q53; 330; water supply; water quality; sanitation; hygiene; child health; diarrhoea; impact evaluation; infrastructure; Yemen